1997
DOI: 10.1002/(sici)1097-0010(199706)74:2<244::aid-jsfa798>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in the Composition of Ileal Digesta and the Ileal Digestibilities of Nutrients in Growing Pigs

Abstract: Diurnal variation in the chemical composition of digesta and its effect on nutrient digestibilities of diets varying in dietary fibre content was examined in pigs fitted with a PVTC‐cannula at the terminal ileum. The pigs were fed three times a day (08:00, 16:00 and 24:00 h). A barley control diet and four barley‐based diets containing two levels (100 or 200 g kg‐1 diet) of alfalfa meal or white clover meal and Cr2O3 as an indigestible marker were fed according to a 5×5 Latin square design. In each experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…Day of collection did not affect (P > 0.05) any of the digestibility coefficients. This is in agreement with the findings of Jørgensen et al (1997). For increased accuracy, the means of the two separate days of collection, and not individual days, were used when comparing period and diet means.…”
Section: Calculations and Statistical Analysessupporting
confidence: 85%
See 1 more Smart Citation
“…Day of collection did not affect (P > 0.05) any of the digestibility coefficients. This is in agreement with the findings of Jørgensen et al (1997). For increased accuracy, the means of the two separate days of collection, and not individual days, were used when comparing period and diet means.…”
Section: Calculations and Statistical Analysessupporting
confidence: 85%
“…For example the apparent ileal lysine digestibility coefficients from the first to last sampling blocks were as follows: 85.5, 82.4, 83.7, 83.9, 85.9, and 84.4%, respectively. However, in order to reduce variation in measured amino acid digestibility coefficients, it is ideal to collect ileal digesta continuously between feedings, or in another manner that accounts for the diurnal pattern of digesta flow, as discussed by Jørgensen et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-day pre-feed period was followed by a 7-day faecal collection period and by 2-day  12-h collections of ileal digesta. Ileal digesta was collected during daytime only as work by Jorgensen et al (1997) concluded that ileal flow and composition of digesta followed similar patterns after feeding and that a representative sample could be collected during the day provided feeding was at regular intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Prerequisites for this method are that the animals are in a balanced physiological state and that the sampling of ileal chyme is representative. Jørgensen et al (1997) studied the diurnal variation in the composition of ileal digesta and the ileal digestibilities of nutrients and concluded that the estimate of digestibility can be based on digesta samples collected from any interval between two consecutive meals provided that all periods between meals are represented in the pooled ileal sample. This is the case in the present study where the pooled ileal sample is based on two 8 h periods.…”
Section: Type Of Cannulamentioning
confidence: 99%